Reduced cognitive deficits after FLASH irradiation of whole mouse brain are associated with less hippocampal dendritic spine loss and neuroinflammation. (October 2019) - Simmons, Danielle A.; Lartey, Frederick M.; Schüler, Emil; Rafat, Marjan; King, Gregory; Kim, Anna; Ko, Ryan; Semaan, Sarah; Gonzalez, Selena; Jenkins, Melissa; Pradhan, Pooja; Shih, Zion; et al.
Highlights: Brain radiation impairs cognition, associated with neuronal degeneration and neuroinflammation. Ultra-rapid FLASH produced reduced cognitive deficits vs . conventional delivery time. Loss of hippocampal dendritic spines and neuroinflammation were less evident after FLASH. These factors may mediate the improved therapeutic index of FLASH brain irradiation. Abstract: Aim: To evaluate the impact of ultra-rapid FLASH mouse whole brain irradiation on hippocampal dendritic spines and neuroinflammation, factors associated with cognitive impairment after brain irradiation. Methods: We administered 30 Gy whole brain irradiation to C57BL6/J mice in sub-second (FLASH) vs . 240 s conventional delivery time keeping all other parameters constant, using a custom configured clinical linac. Ten weeks post-irradiation, we evaluated spatial and non-spatial object recognition using novel object location and object recognition testing. We measured dendritic spine density by tracing Golgi-stained hippocampal neurons and evaluated neuroinflammation by CD68 immunostaining, a marker of activated microglia, and expression of 10 pro-inflammatory cytokines using a multiplex immunoassay. Results: At ten weeks post-irradiation, compared to unirradiated controls, conventional delivery time irradiation significantly impaired novel object location and recognition tasks whereas the same dose given in FLASH delivery did not. Conventional delivery time, but not FLASH, was associated with significant loss of dendritic spine density in hippocampal apical dendrites, with a similar non-significant trend in basal dendrites. Conventional delivery time was associated with significantly increased CD68-positive microglia compared to controls whereas FLASH was not. Conventional delivery time was associated with significant increases in 5 of 10 pro-inflammatory cytokines in the hippocampus (and non-significant increases in another 3), whereas FLASH was associated with smaller increases in only 3. Conclusion: Reduced cognitive impairment and associated neurodegeneration were observed with FLASH compared to conventional delivery time irradiation, potentially through decreased induction of neuroinflammation, suggesting a promising approach to increasing therapeutic index in radiation therapy of brain tumors.